2018
DOI: 10.1080/19396368.2018.1453563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neonatal outcomes of intrauterine insemination with frozen donor sperm

Abstract: AID: artificial insemination by a donor; AIH: artificial insemination by the husband; ART: assisted reproduction technology; FET: frozen embryo transfer; IVF: in vitro fertilization; ICSI: intracytoplasmic sperm injection; IUI: intrauterine insemination; LBW: low birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Based the data of the Society of Assisted Reproductive Technology Clinic Outcome Reporting System, a 42 g increase in birthweight was reported in sperm donation offspring comparing with that in partner sperm offspring [22]. Similarly, Chen et al reported an increase in birthweight in children born after frozen donor sperm intrauterine insemination comparing with those after paternal sperm intrauterine insemination [23]. The heterogeneous results may warrant further investigation on unmeasured or unknown factors that may affect the birthweight in cooperated with sperm cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…Based the data of the Society of Assisted Reproductive Technology Clinic Outcome Reporting System, a 42 g increase in birthweight was reported in sperm donation offspring comparing with that in partner sperm offspring [22]. Similarly, Chen et al reported an increase in birthweight in children born after frozen donor sperm intrauterine insemination comparing with those after paternal sperm intrauterine insemination [23]. The heterogeneous results may warrant further investigation on unmeasured or unknown factors that may affect the birthweight in cooperated with sperm cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other assisted reproductive technologies, AIH costs less, does less harm to patients, and is relatively easy to use -these characteristics make it a more readily accepted treatment option for infertile couples. 12,13 However, the clinical pregnancy rate of AIH is only about 8-22 %, which is a major challenge for patients and medical workers. 12,14 Hence, improving the clinical pregnancy rate of AIH is a hot research topic in the field of infertility.…”
Section: Discussionmentioning
confidence: 99%
“…AIH is a suitable infertility treatment for men with mild oligospermia, retrograde ejaculation, hypospadias, sexual dysfunction, and anti‐sperm antibody in semen, as well as for women with cervical deformity, abnormal cervical mucus, endometriosis, unexplained infertility, and so on. Compared to other assisted reproductive technologies, AIH costs less, does less harm to patients, and is relatively easy to use – these characteristics make it a more readily accepted treatment option for infertile couples 12,13 . However, the clinical pregnancy rate of AIH is only about 8–22 %, which is a major challenge for patients and medical workers 12,14 .…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that neck translucency thickness (NT) as well as the blood flow rate through the venous line (DV-PI) were statistically significantly higher in fetuses burdened with a heart defect in comparison to fetuses in which no such defects were determined when fertilization occurred as a result of sexual intercourse in the group of women in which no assisted reproduction techniques were used (11 of 1298 cases) as well as in the group of women after pharmacologically induced ovulation (3 of 137 cases). However, the obtained results did not indicate that any fetus which developed as a result of intracytoplasmic injection was fraught with a congenital heart defect; therefore, the likely cause of a heart defect not being identified amongst these fetuses may result from the fact that the sperm used for fertilization is selected before it is introduced to the egg [ 30 ].…”
Section: Discussionmentioning
confidence: 99%